Tacrolimus toxicity reverses the inhibitory effects of renin angiotensin system blockade on PAI-1 expression in cardiac tissue - (:unkn) unknown (My University, 2013)
Introduction: PAI-1 is a potent fibrosis promoting glycoprotein in a tissue dependent manner. We previously displayed that tacrolimus (FK506) toxicity increases vacuolar degeneration and arterial hyalinosis in cardiovascular tissue. FK506 toxicity induced transforming growth factor (TGF-(3) expression. Renin angiotensin system (RAS) blockade partially reversed histopathological changes associated with FK506 toxicity. In the same model, we investigated the effects of FK506 and RAS blockade on PAI-1 expression. Materials and Methods: We examined cardiac expression of PAI-1 in a chronic FK506 toxicity model in Wistar rats. Study animals were divided into 4 groups. FK506 group was treated with FK506 intraperitoneally, FK506+Quinapril and FK506+Valsartan groups were treated Quinapril or Valsartan orally in addition to FK506. Control group was treated with saline. Immunohistochemical staining of cardiovascular tissue was semiquantitatively scored for PAI-1 expression. Results: FK506 significantly induced PAI-1 expression in the cardiovascular tissue compared to the control group (semiquantitative scores were 25±5 versus (vs) 49±21, p =0.01). Adding renin angiotensin system blockade with an angiotensin converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) to FK506 increased FK506 induced PAI-1 expression. Semiquantitative PAI-1 expression scores were 49±21, 87±14 and 95±10 for FK506, FK506+ACEI, and FK506+ARB groups respectively (p<0.01). Conclusion: FK506 toxicity is associated with up-regulation of PAI-1 expression at the tissue level which is not attenuated after RAS blockade. These observations suggest that FK506 induces an angiotensin II independent increase on PAI-1 expression in cardiac tissue and/or elevated TGF-fS and reduced BMP-7 levels with FK506 toxicity may reverse the inhibitory effects of RAS blockade on PAI-1 expression. © 2013 Bentham Science Publishers.
Keywords: Cardiac toxicity; PAI-1; Renin-angiotensin system; Tacrolimus